Vers une éducation à la prudence : délibérer dans l'incertitude. Le cas de l'usage de la voie publique - Dominique Violet (Université de Provence, 2013)
Looking at the statistics of accidents, the use of public roads is one of the areas where security is a major issue. Many research papers on this issue focus more on tools and methods than on a profound consideration of the status of the user. The latter usually appears as an actor who may, or who is willing to comply with the Highway Code. In case of breaches in the rules designed to prevent accidents, the presumption of fault of the user is typically required. Without removing the possibility of fault, it is possible to designate the user as a person making choices of ethical nature. De facto, the concept of security is facing or replaced by the concept of caution. In this case it is wiser to educate caution than to train security.